Mental Health in Urologic Oncology - Danyon Anderson; Abrahim N. Razzak; Matthew McDonald; David Cao; Jamal Hasoon; Omar Viswanath; Alan D. Kaye; Ivan Urits (Health Psychology Research)
This article is a systematic review of mental health in urologic oncology patients with prostate cancer (PCa), bladder cancer (BC), renal cell carcinoma (RCC), testicular cancer (TC), or penile cancer (PeCa). For all pathologies, a focus on increasing quality of life post-treatment demonstrated a positive impact in reducing Mental Health Illness (MHI) prevalence. Cancer specific mental health care may be given to patients to reduce suicide risk in BC patients and sexual identify and masculinity counseling may improve mental health for TC or PeCa patients. In order to better accommodate patient’s mental health needs when undergoing GU cancer treatment, we recommend incorporation of mental health metrics such as questionnaires to assess early treatment of MHI, a greater emphasis on psychosocial support with the patient’s loved ones, peers, and healthcare team, alongside advising healthy habits such as exercise which has been shown to drastically reduce MHI incidence across all pathologies. We hope that these measures conducted by urologists and oncologists, alongside possible coordination with psychiatrists and psychologists for psychotherapy, psychopharmacology, and neuro-stimulation treatment modems may be helpful in the long term to reduce MHI incidence in urology oncology patients. Given the higher incidence of MHI in oncology patients and in the patient population after the Covid-19 pandemic, MHI awareness in the sphere of urologic oncologic treatment continues to be crucial when creating a collaborative treatment platform for patients.